Fatigue Cracking Behaviour and Characteristics of Flexible Pavement Subjected to Freight Coal-Truck Loading - Setiawan, Dian M. (International Journal of Sustainable Construction Engineering and Technology, 2024)
Fatigue cracking is one of the varieties of flexible pavement distress caused by frequent traffic loads, and it is also a sign of structural collapse. Using finite element methods, numerical simulations were conducted to evaluate the strain changes that occur throughout the process of flexible pavement cracking. Several flexible pavement configurations with various thickness and different material properties of AC layer were developed, and several loading conditions in terms of the axle load, the speed, and the loading cycles of the freight truck were modelled. The numerical modelling showed that the greatest horizontal tensile strain in the 1st AC layer (surface course) is at the surface-centre of the pavement structure, which is predicted to be prone to top-down cracks. In other side, the greatest horizontal tensile strain in the 2nd AC layer (base course) is at the bottom-below of the tire tread, which is predicted to be vulnerable to bottom-up cracks. The outcomes of this study added to the knowledge gathered from previous studies, especially regarding the critical locations within the AC layer with the greatest magnitude of horizontal tensile strain and their potency to experience either the top-down cracking or bottom-up cracking, as well as related to the effect of slowing the truck speed and increasing both the truck’s hauling load and loading cycles on the fatigue life of asphalt concrete layer. Future research needs to be done to evaluate the balance between both permanent deformation behaviour of the AC layer and to determine the optimum flexible pavement configurations.